Residual stress distribution in a Ti-6Al-4V T-joint weld measured using synchrotron X-ray diffraction - Xu, Lei; Zhang, Shu-Yan; Sun, Wei; McCartney, David G.; Hyde, Thomas H.; James, Jon; Drakopoulos, Michael (Sage, 2015)
To improve the manufacturing quality of welded structures, to prevent failures at weld joints and to predict their lifetime, measurements of the residual stresses generated by welding in the structures are extremely useful. The residual stresses may reduce the component life due to phenomena that occur at low applied stresses such as brittle fracture, fatigue and stress corrosion cracking. Welded thin Ti-6Al-4V panel components are commonly found in aero-engine assemblies and the weld integrity and reliability are critical. In this work, the residual stress distributions in a welded thin Ti-6Al-4V T-joint were measured by the newly developed SScanSS program with synchrotron X-ray diffraction technique. The measurement performed in this study, which included a large number of measurement points, has mapped a complete stress field in a thin sheet T-joint weld. It has not only provided improved understanding of residual stress in such a joint but also filled the missing link between the residual stress obtained by numerical modelling and their validation. The results have shown that the longitudinal stresses play the most important role in the residual stress distribution over the flange and high tensile stresses appear in the region near the weld zone. The measured results were compared with numerically predicted results and these showed good agreement.